Importancia de la biofilia en el aprendizaje de entorno natural y social en niños de primer año de educación básica, de la Unidad Educativa “Combatientes de Tapi”, de la ciudad de Riobamba, periodo 2020-2021 - Peñafiel Montalvo, Marlid Leonela (2021)
This investigation research aimsat the importance of biophilia in the learning of the natural and social environment in children of the first year of Basic General Education at the Unidad Educativa “Combatientes de Tapi” of Riobamba city, period 2020-2021 ", it has as objectives to analyze the importance of biophilia in the learning of the natural and social environment in children, to identify the current teaching-learning situation of biophilia used by teachers, to determine the importance of biophilia as a strategy to be used in the teaching process in areas of natural and social environment, their interrelation in the learning of children, as well as establishing teaching strategies - learning of natural and social environment that allow interrelation between peers, in addition to promoting close contact with an innate and deep aspect of the species. It was based on the state of the art with concepts related to the two study variables, the methodology applied was documentary, bibliographic, because the research was carried out at the scene of the events and with the population consisted of 37 children who were applied the observation sheet and 37 parents who were surveyed, it can be concluded that the parents are committed to the education of the children so that they have learned with good foundations that will help them in the future and relating to nature, where they can feel identified with the environment, in the same way, children feel very comfortable being related to nature and they know how important it is to take care of it and maintain it.